Development of a Method for the Extraction of the Total Proteome of Bacillus Anthracis Spores - Koteneva, E.A.; Tsygankova, O.I.; Kalinin, A.V.; Shcherbakova, V.Yu.; Rodionov, I.S.; Serdyukov, V.V.; Abramovich, A.V. (Biomedical Chemistry: Research and Methods, 2021)
We have developed a method for obtaining the total proteome of Bacillus anthracis spores, which combines efficient protein extraction with reliable disinfection of samples. We used 7 strains of B. anthracis: 4 plasmid-free, 3 diplasmid, one of which with an atypical type of capsule formation in air. The schemes for isolating the total spore proteome were tested using various lysis solutions in the presence of bacterial protease inhibitors, with the inclusion of the stages of treatment of spores with trichloroacetic acid and mechanical disintegration and with their exclusion. The quality and completeness of the extraction of the total proteome of the spores of the samples was assessed in one-dimensional (1D) and twodimensional (2D) electrophoresis. Treatment of spores with trichloroacetic acid increased the reliability of material disinfection and reduces the loss of the final product. Mechanical disintegration after treatment of spores with lysing solutions increases the completeness of extraction of spore proteins in a wide range of molecular weights and facilitated the process of sterilizing filtration. Final filtration of the lysate through a PVDF filter with a pore size of 0.22 μm provided additional decontamination of samples without reducing their quality. Thus, the use of the proposed sample preparation scheme makes it possible to obtain complete protein extracts of spores of B. anthracis strains, suitable for comparative analysis of the proteome and search for a possible correlation with the features phenotypic properties and mechanisms that ensure the preservation of the pathogen anthrax in environmental objects, including soil